Peranan Dana Zakat Produktif Terhadap Perkembangan Usaha Mikro Mustahik Melalui Program Riau Makmur Pada Baznas Provinsi Riau (Studi Kasus Kota Pekanbaru) - Ramadhan, Vicky; Setiawan, Deny; Misdawita, Misdawita (Jurnal Ilmiah Ekonomi Islam, 2023)
Productive zakat, namely zakat given by amil institutions to people who need capital assistance, productive zakat fund assistance as capital to carry out an economic activity, namely to develop economic conditions and potential productivity of mustahik. Analysis is used to determine the form of zakat receipt and distribution by BAZNAS Riau Province descriptive while to find out how the effect of productive zakat funds channeled by BAZNAS Riau Province on mustahik used logistic regression analysis. The effect of the amount of productive zakat assistance on the development of mustahik micro businesses partially based on the t test states that the amount of productive zakat assistance has no significant effect on the development of mustahik micro businesses .coaching has a positive and significant effect on the development of mustahik micro businesses. initial capital does not have a significant effect on the development of mustahik micro businesses. The results of the regression analysis show that the variable amount of productive zakat, mentoring and initial capital jointly affect the development of mustahik micro businesses. Meanwhile, partially the variable amount of productive zakat, assistance and initial capital also influences the development of mustahik micro businesses.